1987
DOI: 10.3168/jds.s0022-0302(87)80166-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters for First Lactation Milk Yields at Three Levels of Herd Production

Abstract: A multivariate linear model was used to estimate sire variance and covariance components and residual variance components for first lactation milk yield and logarithms of yield at three herd production levels using Restricted Maximum Likelihood with the ExpectationMaximization algorithm. Data for four separate analyses were 305-d, mature equivalent first lactation milk records from cows sired artificially in the northeastern United States that freshened in 1970, 1971, 1976, and 1984. Respective numbers of reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
1
8

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 18 publications
(21 reference statements)
5
25
1
8
Order By: Relevance
“…Praticamente não houve alterações do componente de variância residual quando no modelo foi ajustado o termo de interação. Aumento nas estimativas dos componentes de variância genética e residual, com aumento do nível de produção dos rebanhos, foi também observado por DE VEER e VAN VLECK (1987), BOLDMAN e FREEMAN (1990), DONG e MAO (1990), SHORT et al (1990), COSTA (1998) e TORRES (1998).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Praticamente não houve alterações do componente de variância residual quando no modelo foi ajustado o termo de interação. Aumento nas estimativas dos componentes de variância genética e residual, com aumento do nível de produção dos rebanhos, foi também observado por DE VEER e VAN VLECK (1987), BOLDMAN e FREEMAN (1990), DONG e MAO (1990), SHORT et al (1990), COSTA (1998) e TORRES (1998).…”
Section: Resultsunclassified
“…Esses valores representam o ganho genético esperado nos rebanhos de médio e baixo desvios-padrão, por unidade de ganho genético obtido nos rebanhos de alto desvio-padrão, e maiores ganhos seriam esperados Tabela 1 -Médias e desvios-padrão (D.P.) da produção de leite ajustada para 305 dias de lactação e idade adulta, número de lactações, de classes de rebanho-ano-estação (RAE), de rebanhos (REB) e de lactações por ordem de parto (OP), conforme classes de desvio-padrão VAN VLECK (1987) encontraram correlações genéticas que variaram de 0,86 a 0,97 entre as classes de rebanhos, estratificadas de acordo com a média da produção de leite, para as classes de rebanho-ano-estação, em baixo, médio e alto níveis de produção. BOLDMAN e FREEMAN (1990) detectaram correlações genéticas, para produção de leite, que variaram de 0,90 a 1,02 entre os níveis de produção baixo, médio e alto.…”
Section: Resultsunclassified
“…Until recently, in most genetic evaluations using mixed model methodology, variances were assumed to be constant across environmental groups. However, several studies have shown that these assumptions do not hold in many cases (Hill et al, 1983;Hill, 1984;DeVeer & Van Vleck, 1987;Boldman & Freeman, 1990). Variances for production and conformation traits of dairy cattle have been found to be heterogeneous across herds, herdclasses, environments or other types of fixed effect levels (Dodenhoff & Swalve, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…First, a transformation of data can be performed in order to match the usual assumption of homogeneity of variance. A log transformation was proposed by several authors in quantitative genetics (see eg Everett and Keown, 1984;De Veer and Van Vleck, 1987;Short et al, 1990, for milk production traits in cattle). However, while genetic variances tend to stabilize, residual variances of log-transformed records are larger in herds with the lowest production level (De Veer and Van Vleck, 1987;Boldman and Freeman, 1990;Visscher et al, 1991).…”
mentioning
confidence: 99%
“…A log transformation was proposed by several authors in quantitative genetics (see eg Everett and Keown, 1984;De Veer and Van Vleck, 1987;Short et al, 1990, for milk production traits in cattle). However, while genetic variances tend to stabilize, residual variances of log-transformed records are larger in herds with the lowest production level (De Veer and Van Vleck, 1987;Boldman and Freeman, 1990;Visscher et al, 1991). ' The second alternative is to develop robust methods which are insensitive to moderate heteroskedasticity (Brown, 1982 (1990,1992) where X i and Z; are (n i x p) and (n i x q i ) incidence matrices, corresponding to fixed J3 (p x 1 ) and random u i (q i x 1 ) effects respectively.…”
mentioning
confidence: 99%